A comprehensive review on the plant sources, pharmacological activities and pharmacokinetic characteristics of Syringaresinol - Lei Zhang; Yuqing Tian; Lingling Zhang; Huanyu Zhang; Jinghua Yang; Yi Wang; Na Lu; Wei Guo; Liang Wang (Pharmacological Research)
Syringaresinol, a phytochemical constituent belonging to lignan, is formed from two sinapyl alcohol units linked via a β-β linkage, which can be found in a wide variety of cereals and medicinal plants. Medical researches revealed that Syringaresinol possesses a broad spectrum of biological activities, including anti-inflammatory, anti-oxidation, anticancer, antibacterial, antiviral, neuroprotection, and vasodilation effects. These pharmacological properties lay the foundation for its use in treating various diseases such as inflammatory diseases, neurodegenerative disorders, diabetes and its complication, skin disorders, cancer, cardiovascular, and cerebrovascular diseases. As the demand for natural therapeutics increases, Syringaresinol has garnered significant attention for its pharmacological properties. Despite the extensive literature that highlights the various biological activities of this molecule, the underlying mechanisms and the interrelationships between these activities are rarely addressed from a comprehensive perspective. Moreover, no thorough comprehensive summary and evaluation of Syringaresinol has been conducted to offer recommendations for potential future clinical trials and therapeutic applications of this bioactive compound. Thus, a comprehensive review on Syringaresinol is essential to advance scientific understanding, assess its therapeutic applications, ensure safety, and guide future research efforts. This will ultimately contribute to its potential integration into clinical practice and public health. This study aims to provide a comprehensive overview of Syringaresinol on its sources and biological activities to provide insights into its therapeutic potential, and to provide a basis for high-quality studies to determine the clinical efficacy of this compound. Additionally, we explored the pharmacokinetics, toxicology, and drug development aspects of Syringaresinol to guide future research efforts. The review also discussed the limitations of current research on Syringaresinol and put forward some new perspectives and challenges, which laid a solid foundation for further study on clinical application and new drug development of Syringaresinol in the future.